Promoting Subjective Well-being: Essential in leading to Up-gradation of one’s Living Conditions - Radhika Kapur, (Indian Journal of Social Science and Literature (IJSSL), 2024)
Promoting subjective well-being is important for all individuals, belonging to all communities, categories and socio economic backgrounds. The senior citizens are required to be well versed in terms of all types of methods and strategies, which are facilitating in promoting subjective well-being. The individuals in old age are required to be well-equipped in terms of different techniques, which would be facilitating in generating desired outcomes. The elderly individuals are required to form cordial and amiable terms and relationships with other individuals. The family and community members are required to make provision of support and assistance to elderly individuals. The reason being, in old age, individuals experience decline in capabilities and aptitude, hence, they are required to communicate and take help from others in promoting enhancement of their overall standards of living. One of the important aspects that needs to be taken into account is, in old age, individuals need to promote a normal mind set. This will be facilitating in leading to up-gradation of different types of skills and abilities. As a consequence, analytical, criticalthinking and problem-solving skills will be put into operation in an appropriate manner. Therefore, promoting subjective well being is essential in leading to up-gradation of one’s living conditions. The main concepts that are taken into account in this research paper are, understanding the meaning and significance of subjective well-being, measures to be implemented in promoting subjective well-being and impediments encountered by senior citizens in promoting subjective well-being.